Nation of rebels : why counterculture became consumer culture - Heath, Joseph; Potter, Andrew (New York : Harper Business, 2004)
- The birth of counterculture##- Freud goes to California##- Being normal##- I hate myself and want to buy##- Extreme rebellion##- Uniforms and uniformity##- From status-seeking to coolhunting##- Coca-colonization##- Thank you, India##- Spaceship Earth.
CCS Gent
boek